Pertambangan Timah Inklusif dan Berkelanjutan di Belitung Timur dengan Analisis Promethee: An Analysis of Inclusive and Sustainable Tin Mining in East Belitung Using the PROMETHEE Method - Nursalam, Ruddy; Yusuf, Maulana; Asngari, Imam (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2025)
This paper discusses the potential of tin mining in the IUP Laut DU 1562 area in East Belitung Regency. However, this potential is difficult to realize due to regulatory constraints, especially after the Bangka Belitung Province ratified Regional Regulation Number 3/2020 regarding RZWP3K which does not include this area as a mining area, but a fishing zone. Therefore, an inclusive and sustainablity study is needed for the utilization of marine space to provide benefits for the country, local governments, society, and minimize environmental impacts. In this study, PT Timah TBK conducted data and information collection stages and analysis stages, including discussions with related stakeholders, direct observations in the field, and related official documents. The result of this study is the development of three development scenarios, namely inclusive tin mining, exclusive tin mining, and non-tin mining. These scenarios are then analyzed using the Promethee method to produce policy recommendations.